Implementasi Aplikasi Berbasis Mobile Untuk Pelayanan Jasa Kesehatan - Primin, Bella; Wibowo, Adityo Permana (Jurnal Informatika: Jurnal Pengembangan IT, 2023)
Health is one of the important aspects of society's life. Karangampel Health Center is one of the health centers that provide public health services in general. There are several health services provided by the puskesmas including regular medical practices, specialist doctors practices, KIA service practices (Mother and Child Health), and KB service practices. Currently, the queue system at the puskesmas does not yet use the computerization so it is less effective. Many patients who have signed up complain because they don't know for sure the operational schedule at the health center. The purpose of this study was to build a mobile-based computerization application that contains information about the doctor's practice schedule, registering online, the patient's examination history, as well as submitting an online reference letter. The app also had a feature to get an ambulance call quickly. This research method includes observations and System Designers using Systems development of life cycle (SDLC) by the prototype method, and the creation of the system so that it produces a Mobile-based puskesmas information system. Applications are made, then the test is carried out using a black box. The test results result in a value of 80% so it shows that the application is worth using